With a Little Help from Our Friends : Creating Community as We Grow Older - Baker, Beth, 1951- (Book collections on Project MUSE., 2014)
"In this book, an award-winning journalist tells the story of people devising innovative ways to live as they approach retirement, options that ensure they are surrounded by a circle of friends, family, and neighbors. Based on visits and interviews at many communities around the country, Beth Baker weaves a rich tapestry of grassroots alternatives, some of them surprisingly affordable -- an affordable mobile home cooperative in small-town Oregon -- a senior artists colony in Los Angeles -- neighbors helping neighbors in "Villages" or "naturally occurring retirement communities"--Intentional cohousing communities -- best friends moving in together -- multigenerational families that balance togetherness and privacy -- niche communities including such diverse groups as retired postal workers, gays and lesbians, and Zen Buddhists. Drawing on new research showing the importance of social support to healthy aging and the risks associated with loneliness and isolation, the author encourages the reader to plan for a future with strong connections. Baker explores whether individuals in declining health can really stay rooted in their communities through the end of life and concludes by examining the challenge of expanding the home-care workforce and the potential of new technologies like webcams and assistive robots"--